Analytical Model to Describe Damage in CFRP Specimen When Subjected to Low Velocity Impacts. (2016) - Salvetti, M.; Gilioli, A.; Sbarufatti, C.; Dragan, K.; Chalimoniuk, M.; Manes, A.; Giglio, M.
Abstract: In the light of an increment of the safety of CFRP components subjected to low-velocity impacts, the identification of a damage onset threshold is desired. Hence the suitability of an analytical model for the estimation of the critical load of delamination onset and the resulting delaminated area, as well as for the approximation of the load-displacement curve, has been investigated. The Olsson's analytical model, available in the literature, is considered and applied in this study for the prediction of the mechanical behaviour of composite specimens subject to low-velocity impacts. Comparisons with experimental results have been carried out to demonstrate the accuracy of the presented model. Impact tests were performed in accordance with ASTM D7136 standard and damage was assessed by means of ultrasonic testing and computed tomography.